The The Ozone treatment for Elimination of toxic waste – An alternate for preservation of goat skins and enhancement of bleaching property of starch (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In line with the staggering number of about 14 percent of India's GDP relying on the food processing industry. Our area of research aims at exploring the wide spread applications of the use of ozone a chemical compound that has the property of being a strong oxidant along with its potent capabilities of being a disinfecting agent in the food processing industry. Specifically focusing on the implication of the ozonized based processing techniques on the food and animal related processed products which include goat skin and manufacturing of starch. During the phase of the research we compared the impacts, advantages on using Ozone based processing technique over the existing methods like salt curing, and starch manufacturing from tapioca starch involves peeling, washing, rasping, screening, dewatering, drying, pulverization, dry screening and packaging. Ozonised skins kept exposed to atmospheric air were more impervious to microbial activity is in existence. This opens up the likelihood of applying Ozonisation innovation to protect goatskins so as to take out earth unsafe salt curing. And improving the whiteness property of sago starch without creating any harmful by products using Ozonisation based techniques.